Organocatalyzed Regioselective α,γ-Difunctionalization of Deconjugated Butenolides: Synthesis of Butyrolactone–Butyrolactam Hybrid Molecules - Mondal, Swati Lekha; Patra, Koushik; Yadav, Rahul; Baidya, Mahiuddin (Synlett, 2023)
A highly regioselective α,γ-difunctionalization of deconjugated butenolides that allows access to hybrid molecular frameworks composed of unsaturated butyrolactone and butyrolactam motifs is reported. The reaction is catalyzed by inexpensive quinidine, and products are isolated in high yields as a single diastereomer. The γ-selective monofunctionalization was also accomplished through substrate modification.
Keywords: butenolides; γ-lactams; organocatalysis; hybrid molecules